Exploring factors of user's peer-influence behavior in social media on purchase intention: Evidence from QQ. (October 2016) - Zhu, Zhiguo; Wang, Jianwei; Wang, Xiening; Wan, Xiaoji
Abstract: How to leverage the interactions and peer-influences among online friends to motivate users' purchase willingness and improve marketing performance has been a hot research issue in human behavior based on social media. In our research, we extracted the dataset of users' purchasing membership services on QQ, the biggest online instant message system in China, to explore the main factors of user's peer-influence behavior on promoting purchase in social media. Through a series of elaborate experiments, we obtained some valuable results. First, though the high-degree users who have a lot of online friends will influence more followers to purchase the services, the proportion of friends involved in the purchase is actually comparatively lower than some low-degree users. At the same time, the "neighbor-press effect" induced from a user's connected friends having purchased will bring obvious positive impact on promoting this user's purchase willingness. Finally, the length of most purchase chains (about 80%) is within two nodes, which verifies that the purchase diffusion is more confined in the small-scale "circle of friends". Our results indicate that peer-influence purchase is less likely to be due to the influence of higher degree users but is more related to the number of prior adoptions (predecessors) in the user's social neighborhood. The achievements of this study will provide deep technical supports for strategic planning and implementation in the social marketing practice. Highlights: The key factors of promoting user's purchase intents through peer-influence in OSN are explored. Peer-influence purchase behavior is less likely to be attributed to the influence of higher degree users. The "neighbor-press effect" will bring obvious positive impact on promoting users' purchase willingness. More purchase chains are more confined in the small-scale "circle of friends".